Preparation and characterisation of Citrulus colocynthis oil biodiesel: Optimisation of alkali-catalysed transesterification - Elsheikh, Y.A. (2014)
A non-edible oil of Citrulus colocynthis was investigated as a prospective feedstock for biodiesel production by transesterification reaction with methanol. The content of fatty acid methyl ester in the produced oil obtained by four alkaline-catalysed transesterifications, i.e. sodium hydroxide, sodium methoxide, potassium methoxide and potassium hydroxide was evaluated. Important fuel properties of the produced biodiesel such as ester content, density, kinematic viscosity and acid value were measured and compared. The ester ingredients in the biodiesel product were myristic, palmitic, stearic, oleic and linolenic. The best quality of Citrulus colocynthis oil at the highest yield of 97.8 was produced at a constant mixing rate of 600rpm, methanol/oil molar ratio of 6:1, 60Â°C reaction temperature for 60min, using 1.0wt of NaOH. Â© 2013 Canadian Society for Chemical Engineering.